Common arbuscular mycorrhizal networks amplify competition for phosphorus between seedlings and established plants - Merrild, Marie P.; Ambus, Per; Rosendahl, Søren; Jakobsen, Iver (The New phytologist, 2013)
Common mycorrhizal networks (CMNs) influence competition between plants, but reports regarding their precise effect are conflicting. We studied CMN effects on phosphorus (P) uptake and growth of seedlings as influenced by various disruptions of network components. Tomato (Solanum lycopersicon) seedlings grew into established networks of Rhizophagus irregularis and cucumber (Cucumis sativus) in two experiments. One experiment studied seedling uptake of 32P in the network in response to cutting of cucumber shoots; the other analysed seedling uptake of P and nitrogen (N) in the presence of intact or severed arbuscular mycorrhizal fungus networks and at two soil P concentrations. Pre-established and intact networks suppressed growth of tomato seedlings. Cutting of cucumber shoots mitigated P deficiency symptoms of seedlings, which obtained access to P in the extraradical mycelium and thereby showed improved growth. Solitary seedlings growing in a network patch that had been severed from the CMN also grew much better than seedlings of the corresponding CMN. Interspecific and size-asymmetric competition between plants may be amplified rather than relaxed by CMNs that transfer P to large plants providing most carbon and render small plants P deficient. It is likely that grazing or senescence of the large plants will alleviate the networkinduced suppression of seedling growth.